2007
DOI: 10.1093/ecam/nem047
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining a Physiological Blood Glucose Level with ‘Glucolevel’, a Combination of Four Anti‐Diabetes Plants Used in the Traditional Arab Herbal Medicine

Abstract: Safety and anti-diabetic effects of Glucolevel, a mixture of dry extract of leaves of the Juglans regia L, Olea europea L, Urtica dioica L and Atriplex halimus L were evaluated using in vivo and in vitro test systems. No sign of toxic effects (using LDH assay) were seen in cultured human fibroblasts treated with increasing concentrations of Glucolevel. Similar observations were seen in vivo studies using rats (LD50: 25 g/kg). Anti-diabetic effects were evidenced by the augmentation of glucose uptake by yeast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 31 publications
1
70
0
1
Order By: Relevance
“…Advanced tumors are treated usually by chemotherapy and although these drugs are effective, they are associated with severe adverse events and drug resistance [2,3]. In the search for new cancer therapeutics with low toxicity and minimal side effects, traditional Islamic medicines might be promising candidates [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced tumors are treated usually by chemotherapy and although these drugs are effective, they are associated with severe adverse events and drug resistance [2,3]. In the search for new cancer therapeutics with low toxicity and minimal side effects, traditional Islamic medicines might be promising candidates [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a significant decrease in HbA1c levels is reported in T2DM who received UD extract (for 8 weeks). Said et al (22) reported that one tablet of glucolevel (a mixture of the dried leaves extract of Juglansre- gia L., Oleaeuropea L., Urticadioica L,. and Atriplexhalimus L.) three doses per day for 4 weeks, significantly reduced the HbA1c levels in 6 out of 16 patients (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to enhance the insulin production in the body and thus maintaining blood glucose level. Medicines prepared from these herbs or their products are used clinically [100]. Along with herbs, mineral extracts from animals are also used to prepare traditional medicines for the treatment of DM [100,101].…”
Section: Unani Medicinal Systemmentioning
confidence: 99%